Implementation of European Language Portfolio in Lithuania: Problems and Implications - Mažuolienė, Zita (Verbum, 2011)
The European Language Portfolio (ELP) has been one of the biggest language education projects of the last decade in Europe. Lithuania has invested considerable finances and effort to exploit the benefits of the ELP. There have been a number of Portfolios designed for the Lithuanian system of education followed by piloting projects and seminars for language teachers run on a large scale at all levels of education. However, the implementation of the ELP in Lithuania seems to be very slow. The article looks into the reasons for the reluctance of language teachers to employ the ELP in the classroom practice and the possible ways of promoting the ELP implementation. The role of school authorities is emphasized and some possible solutions for stimulating stake holders’ interest in the ELP suggested.
Keywords: European Language Portfolio; ELP implementation; integration; syllabus; ELP dissemination.